Power and interest levels in safely managed sanitation services in Zambia: A stakeholder mapping - Beatrice Chiwala; Mpundu Makasa; Joseph Mumba Zulu (PLoS ONE, 2025)
Background Access to safely managed sanitation (SMS) in sub-Saharan Africa including Zambia remains a challenge. Variations in power and interest among stakeholder significantly influence access to SMS. However, there is limited contextualization of how power and interest levels among stakeholders influenced access to SMS. The study aimed to explore and analyze how stakeholders perceived their power and interest in the context of providing SMS. The study applied the Mendelow Stakeholder Matrix to identify, characterize and analyze the actors involved in the provision of SMS in peri-urban areas in Lusaka, Zambia. Methods A narrative qualitative research design was employed in this study. Ninety–four (94) respondents participated in the study – 25 key informants who were representatives from Government Institutions/Departments, Cooperating Partners, NGOs and community level stakeholders; 60 discussants who participated in focus group discussions, while nine (9) community leaders took part in transect walks conducted in the target areas of Kanyama, Chawama and George. Nvivo14 was utilized for data management and analysis. Results The main results suggested that stakeholders displayed interrelationships that were symbiotic as they depended on each other to deliver their mandates. Stakeholders categorized into Mendelow quadrants displayed varying levels of homogeneity in power and interest. In addition, some stakeholders such as the Local Authority shifted quadrants when seen to perform dual roles for example to implement and enforce the policies aimed at improved public health. Conclusion The stakeholders’ quadrant position coupled with persisted changes in their positions influenced their capacity to contribute effectively to the implementation of strategies to enhance access to SMS. This equally meant that implementers of SMS interventions have to regularly assess their engagement mechanisms to foster dialogue and coordination among stakeholders. Policy implications, especially to Government, may mean allocation of adequate resources to key players to enable them deliver on their respective mandates. Similarly, implications to practitioners might be the need to periodically review stakeholders and forge alliances coupled with conducting multi-sectoral meetings aimed to streamline their functions for the successful delivery of SMS.